2023
DOI: 10.3390/biomimetics8070522
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of Butterfly-Mode Flapping Propulsion of Dolphin Pectoral Fins with Elliptical Trajectories

Dan Xia,
Zhihan Li,
Ming Lei
et al.

Abstract: This article aims to numerically study the hydrodynamic performance of the bionic dolphin equipped with a pair of rigid pectoral fins. We use dynamic-grid technology and user-defined functions to simulate a novel butterfly-mode flapping propulsion of the fins. This pattern of propulsion is composed of three angular degrees of freedom including the pitch angle ϕp, the azimuth angle ϕa and the roll angle ϕr, which can be divided into four stages for analysis within a single cycle. The stroke of one single pector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Webb et al [ 9 ] reported that the pectoral fin generates a cutting force for postural control and discussed its role in improving postural stability. In addition, while many pectoral fin studies have focused on rays [ 10 , 11 ], recent years have shown the effects of pectoral fins in a wide variety of aquatic organisms, including dolphins and turtles [ 12 , 13 ]. The pectoral fins play an auxiliary role in propulsion by flexion of the body to achieve maneuverability such as a change of direction and postural stability, but they also serve as an organ that further enhances the propulsive performance of aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Webb et al [ 9 ] reported that the pectoral fin generates a cutting force for postural control and discussed its role in improving postural stability. In addition, while many pectoral fin studies have focused on rays [ 10 , 11 ], recent years have shown the effects of pectoral fins in a wide variety of aquatic organisms, including dolphins and turtles [ 12 , 13 ]. The pectoral fins play an auxiliary role in propulsion by flexion of the body to achieve maneuverability such as a change of direction and postural stability, but they also serve as an organ that further enhances the propulsive performance of aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%